2016
DOI: 10.1155/2016/9368023
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi Sarcoma among HIV Infected Patients in Lagos University Teaching Hospital, Nigeria: A 14-Year Retrospective Clinicopathological Study

Abstract: Background. Despite the increased incidence of Kaposi sarcoma (KS) resulting from the Human Immunodeficiency Virus/Acquired Immunodeficiency Syndrome (HIV/AIDS) pandemic, there is still significant underreporting of KS in this environment. Objectives. This study was aimed at determining the incidence and clinicopathologic patterns of KS among HIV infected patients in Lagos University Teaching Hospital (LUTH), Nigeria, over a 14-year period: January 2000 to December 2013. Methodology. The materials for this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
7
4
0
Order By: Relevance
“…We also found that the disease was more frequent in males compared with females (10 : 1 ratio), especially in the AIDS‐associated form where all patients were males. Although KS is known to have a male predominance, the male to female ratio in our patient population is even greater than that found in studies from other countries (male‐female ratio 3 : 1 in large epidemiological studies) . In addition, AIDS‐related cases were mostly younger (between 20 and 45 years) than HIV negative cases (older than 50 years), which corroborates with data from the literature …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We also found that the disease was more frequent in males compared with females (10 : 1 ratio), especially in the AIDS‐associated form where all patients were males. Although KS is known to have a male predominance, the male to female ratio in our patient population is even greater than that found in studies from other countries (male‐female ratio 3 : 1 in large epidemiological studies) . In addition, AIDS‐related cases were mostly younger (between 20 and 45 years) than HIV negative cases (older than 50 years), which corroborates with data from the literature …”
Section: Discussionsupporting
confidence: 90%
“…Kaposi's sarcoma (KS) is a vascular tumor which is associated with human herpesvirus 8 (HHV‐8) infection . Clinically, there are four recognized types of KS including classic, acquired immune deficiency syndrome (AIDS)‐associated (epidemic), African (endemic), and iatrogenic (immunosuppressive medication‐related) .…”
Section: Introductionmentioning
confidence: 99%
“…Among patients with the classical KS in our study, the male/female ratio was 2.08%, which was lower than previously reported 8,11 . The mean age of our patients with the classical KS was 68.8 years, which was similar to that in most of studies reported previously but greater than that reported by Wu et al 3,9,11,12 KS patients with HIV positivity had a mean age of 41 years, which was similar to that reported by Akinde et al 5 among HIV -positive KS patients. It has been reported that KS may be accompanied by secondary malignancies 13 .…”
Section: Discussionsupporting
confidence: 89%
“…KS was first defined by Moritz Kaposi in 1872, and is typically characterized by vascular skin lesions of low malignant potential. It particularly affects elderly men of Italian, Jewish, or Mediterranean descent 3,5 . Its incidence varies by geographical region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation